Cognitive Linguistics between Universality and Variation: Introduction - Brdar, Mario; Žic Fuchs, Milena; Raffaelli, Ida (2012)
This is the introduction to the volume that takes up the challenge of assessing the present state of Cognitive Linguistics on the cutting edge between universality and variability.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG